2018
DOI: 10.18666/trj-2018-v52-i1-8446
|View full text |Cite
|
Sign up to set email alerts
|

Recreation in Families with Children with Developmental Disabilities: Caregivers’ Use of Online and Offline Support Groups

Abstract: The purpose of this study was to explore what role online and offline support groups play in the lives of families with children who have developmental disabilities. Eight semi-structured individual interviews were conducted with married mothers who had one to five children. The study revealed that caregivers saw online and offline support groups as playing important but different roles in their lives and the lives of their families. Online support groups were particularly appreciated during the initial steps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In 1 (5.9%) study (Rocha and colleagues [ 24 ]), the gender of parents was not identified, likely due to the study’s recruitment of participants through 2 online registries (Simons Variation in Individuals Project and GenomeConnect). The target population in the studies was most commonly defined as parents of children across a range of disorders and special needs (n=13, 76.5%), while 1 (5.9%) study’s population focused on families in general [ 26 ], 2 (11.8%) on patients themselves [ 24 , 25 ], and 1 (5.9%) solely on married mothers with up to 5 children [ 19 ]. Most studies were conducted in the United States (n=5, 29.4%) [ 15 - 17 , 19 , 29 ], while participants for 6 studies (35.3%) were derived from multiple countries through online recruitment [ 20 , 23 , 24 , 27 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In 1 (5.9%) study (Rocha and colleagues [ 24 ]), the gender of parents was not identified, likely due to the study’s recruitment of participants through 2 online registries (Simons Variation in Individuals Project and GenomeConnect). The target population in the studies was most commonly defined as parents of children across a range of disorders and special needs (n=13, 76.5%), while 1 (5.9%) study’s population focused on families in general [ 26 ], 2 (11.8%) on patients themselves [ 24 , 25 ], and 1 (5.9%) solely on married mothers with up to 5 children [ 19 ]. Most studies were conducted in the United States (n=5, 29.4%) [ 15 - 17 , 19 , 29 ], while participants for 6 studies (35.3%) were derived from multiple countries through online recruitment [ 20 , 23 , 24 , 27 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The target population in the studies was most commonly defined as parents of children across a range of disorders and special needs (n=13, 76.5%), while 1 (5.9%) study’s population focused on families in general [ 26 ], 2 (11.8%) on patients themselves [ 24 , 25 ], and 1 (5.9%) solely on married mothers with up to 5 children [ 19 ]. Most studies were conducted in the United States (n=5, 29.4%) [ 15 - 17 , 19 , 29 ], while participants for 6 studies (35.3%) were derived from multiple countries through online recruitment [ 20 , 23 , 24 , 27 , 30 , 31 ]. The remaining studies were from Australia (11.8%) [ 26 , 28 ], Italy (5.9%) [ 25 ], Kuwait (5.9%) [ 22 ], Norway (5.9%) [ 21 ], and the Netherlands (5.9%) [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations